1988
DOI: 10.1111/j.1432-1033.1988.tb14318.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐binding properties of gene‐5 protein encoded by bacteriophage M 13

Abstract: The irreversible dissociation kinetics of complexes of M13-encoded gene-5 protein with the polynucleotides poly(dA) and M13 DNA was studied by means of stopped-flow experiments. A linear decay was found for all gene-5-protein . poly(dA) complexes and for the gene-5-protein . M13 DNA complexes for which the DNA lattice was completely saturated at the beginning of the dissociation experiments. Only at the end of the dissociation curve was a deviation from linearity observed. A single-exponential decay was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The CD and mobility shift experiments are consistent with two exclusive modes of binding for the Pf3 ssDBP wildtype and Y22F proteins, as previously has been shown to be the case for the fd g5p (Kansy et al, 1986;Bulsink et al, 1988). That is, the binding may be qualitatively described as being consistent with two modes having large ments (Kansy et al, 1986).…”
Section: Compared With Poly[d(a)]supporting
confidence: 80%
See 1 more Smart Citation
“…The CD and mobility shift experiments are consistent with two exclusive modes of binding for the Pf3 ssDBP wildtype and Y22F proteins, as previously has been shown to be the case for the fd g5p (Kansy et al, 1986;Bulsink et al, 1988). That is, the binding may be qualitatively described as being consistent with two modes having large ments (Kansy et al, 1986).…”
Section: Compared With Poly[d(a)]supporting
confidence: 80%
“…In this illustration, the CD change per nucleotide bound in the n = 4 mode is 0.7 that of a nucleotide bound in the n = 2 mode. It should be noted that a maximum CD effect at P/N s 0.25 by binding in an n = 4 mode does not require that the DNA lattice be saturated at this P/N ratio (Kansy et al, 1986;Bulsink et al, 1988). [nucleotide] increased above 0.25, the slopes of the titration plots with the mutant protein decreased, to give total CD changes at saturation that were qualitatively the same as for titrations with the wild-type protein.…”
Section: Compared With Poly[d(a)]mentioning
confidence: 93%
“…As the number of RF DNA molecules increases, so does the concentration of the phage proteins present in the host cell. When gVp reaches a threshold concentration in the host cell, it binds cooperatively to a hairpin on the ssDNA and coats its entire length with approximately 1500 proteins per ssDNA, thereby forming an intermediate complex that prevents conversion into RF DNA [9]. gVp is essential for progeny ssDNA production [10].…”
Section: Introductionmentioning
confidence: 99%
“…DNA binding is triggered by the cellular GVP concentration in the host Escherichia coli. Substantial biochemical and biophysical data have been accumulated regarding the interactions between GVP and DNA (Fulford & Model, 1988;Gray, 1989;Model et al, 1982;Zaman et al, 1992;Anderson et al, 1975;Dick et al, 1988;Bulsink et al, 1986Bulsink et al, , 1988Kansy et al, 1986). NMR and fluorescence studies have suggested that certain amino acids of GVP are in contact with DNA in the GVP-ssDNA complex (Dick etal., 1988;Stassenetal., 1992a,b).…”
mentioning
confidence: 99%